‟DE PUGNA DAEMONUM” NELLA ‟VITA ANTONII” DI ATANASIO D’ALESSANDRIA - FLUERAȘ, Cecilia (Studia Universitatis Babeș-Bolyai Theologia Catholica, 2019)
De pugna daemonum in the Life of Antony of Athanasius of Alexandria. The purpose of this article is to highlight aspects related to the fight against demons, an essential element in the spiritual life of ancient ascetics, who were involved on a path of Christian perfection process, until their identification with Jesus Christ. In the context of the anti-Aryan controversy, bishop Athanasius of Alexandria (4th century) demonstrates the deity of the Incarnate Word by telling the ascetic life of Antony, the Egyptian hermit, his contemporary, along with the stages that mark the progress in spiritual life. The privileged place of the presence of demons is the desert, but Athanasius identifies the work of demons, on one hand, in idolatry, paganism, persecution, and on the other hand, in the temptations and diabolical manifestations that seek to hinder Antony’s (and Christian’s) journey to completion, as well as the spread of the Kingdom of God in the world. That is why Antony’s fight against demons is a leimotif throughout his entire life. Antony, faithful to the spiritual exercises (ascetic, prayer, retreat into the wilderness, faith in the power of the Cross of Christ) wins in this struggle through the power and through the grace of Christ, the Incarnate Word. De pugna daemonum în Viața lui Antonie, de Atanasie al Alexandriei. Acest articol are ca scop relevarea unor aspecte legate de lupta împotriva demonilor, element esențial în viața spirituală a asceților din vechime, care se implicau într-un drum de desăvârșire creștină până la identificarea cu Isus Cristos. În contextul polemicii antiariene, episcopul Atanasie al Alexandriei (sec. IV) demonstrează dumnezeirea Cuvântului Întrupat, povestind viața ascetică a lui Antonie, monahul eremit egiptean, contemporan lui, cu etapele ce marchează progresul în viața spirituală. Locul privilegiat al prezenței demonilor este deșertul, dar Atanasie identifică lucrarea demonilor, pe de o parte, în idolatrie, păgânism, persecuții, pe de alta în tentațiile și manifestările diabolice care caută să împiedice parcursul lui Antonie (și al creștinului) spre desăvârșire, dar și răspândirea Împărăției lui Dumnezeu în lume. De aceea, lupta lui Antonie împotriva demonilor este un leitmotiv de-a lungul întregii Vieți. Antonie, fidel exercițiilor spirituale (asceza, rugăciunea, retragerea în pustiu, credința în dumnezeirea lui Cristos și puterea Crucii) învinge în această luptă cu ajutorul harului lui Cristos, Cuvântul Întrupat. Cuvinte-cheie: Atanasie, Vita Antonii, Întrupare, Isus Cristos, har, credință, asceză, desăvârșire, luptă, demoni